The Effect of Job Rotation and Changes in Organizational Structure on Employee Performance through Organizational Commitment as an Intervening Variable Study of KPP Pratama Pati Employees - Purnomo; Mamik Indaryani; Sutono (Formosa Journal of Science and Technology, 2023)
This study analyzes the effect of job rotation and organizational structure changes on employee performance with organizational commitment as the intervening variable. The research data uses primary data in the form of a questionnaire. The method of determining the sample using purposive sampling and obtained a sample of 110 respondents. The data analysis used in this study is a structural equation model. The results of this study state that job rotation and changes in organizational structure have a positive effect on organizational commitment. The results of this study also state that changes in organizational structure and organizational commitment have a positive effect on employee performance, job rotation has no effect on employee performance.